ISOLATION OF PROBIOTIC BACTERIA CANDIDATES ISOLATED FROM BARRAMUNDI (Lates calcarifer) ANTAGONISTIC AGAINTS Vibrio alginolyticus - Afrimansyah '; Nursyirwani '; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Probiotic is an alternative subtance to prevent fish diseases which is environmentally friendly. The research purpose was to isolate potential probiotic to control bacteria pathogen in barramundi (Lates calcarifer) to control the bacteria pathogen. The probiotic bacteria candidates were isolated from intestine of barramundi by using the spread and streak methods on MRS and TSA media. The antibacterial activity was examinined by using disc diffusion agar method on Zobell 2216E medium. The results showed thirty eight isolates were found which consisted of coccus, white, orange and yellow colonies. Twelve isolates had inhibition against Vibrio alginolyticus,two isolates showed highest inhibition zone and antivibrio activities. The highest inhibition zone (10.04 ± 1,48 mm) and (9,50 ± 2,12 mm) and the antivibrio activities (4.04 mm) and (3.50 mm) were indicated by KPBU2-5 and KPMU2-6 isolates respectively.Keywords: Probiotics, Isolation, Barramundi, Antagonistic.